Posttranslational Modifications and Plant-Environment Interaction - Hashiguchi, A.; Komatsu, S.
Posttranslational modifications (PTMs)of proteins such as phosphorylation and ubiquitination are crucial for controlling protein stability, localization, and conformation. Genetic information encoded in DNA is transcribed, translated, and increases its complexity by multiple PTMs. Conformational change introduced by PTMs affects interacting partners of each proteins and their downstream signaling; therefore, PTMs are the major level of modulations of total outcome of living cells. Plants are living in harsh environment that requires unremitting physiological modulation to survive, and the plant response to various environment stresses is regulated by PTMs of proteins. This review deals with the novel knowledge of PTM-focused proteomic studies on various life conditions. PTMs are focused that mediate plant-environment interaction such as stress perception, protein homeostasis, control of energy shift, and defense by immune system. Integration of diverse signals on a protein via multiple PTMs is discussed as well, considering current situation where signal integration became an emerging area approached by systems biology into account.
Keywords: POSTTRANSLATIONAL MODIFICATIONS; PLANT; ENVIRONMENT; INTERACTION; PROTEOMICS